PENGARUH STRESS KERJA TERHADAP TURNOVER INTENTIONS PADA ERA DIGITALISASI PERBANKAN - Dinda Zanubba Faruq; Dr. Sri Suwarsi, S.E., M.Si., CGA (Bandung Conference Series: Business and Management, 2022)
Abstract. Digitalization is the main factor that causes very high work stress and has an influence on the increase in Turnover Intention. This study aims to determine and analyze 1) To analyze employee work stress in the era of digitalization of banking at Bank Rakyat Indonesia KCP Tasikmalaya. 2) To analyze Employee Turnover Intentions in the banking digitalization era at Bank Rakyat Indonesia KCP Tasikmalaya. 3) To analyze the influence of work stress on Employee Turnover Intentions of banking digitalization at Bank Rakyat Indonesia KCP Tasikmalaya. The research method used is descriptive and verification analysis and operates the calculations using the SPSS 26.0 program. Collecting data obtained through questionnaires, observations, interviews, and literature studies. The number of the population is relatively small or the study wants to make generalizations with very small errors. Another term for saturated sample is census, where all members of the population are sampled. The sample is 67 employees of BRI KCP Tasikmalaya. The results of this study conclude that 1) Work Stress is with the largest score of 288, while the dimension that produces the lowest score is with a score of 286. Work Stress Variable produces an average value of 287 and is on the continuum line of 82.0% thus The statement of Job Stress is included in the “Very High” category. 2) Turnover Intention, which is with the largest score of 297, while the dimension that produces the lowest score is with a score of 286. The Turnover Intention variable produces an average value of 292 and is on the continuum line of 84%, thus the statement from Turnover Intention belongs to the category " Very high/good”. 3) There is a moderate and significant influence of 46.2% of Work Stress on Turnover Intention. Keywords: Work Stress, Turnover Intention Abstrak. Digitalisasi menjadi faktor utama yang menyebabkan stress kerja yang sangat tinggi serta memberikan pengaruh terhadap kenaikan Turnover Intention. Penelitian ini bertujuan untuk mengetahui dan menganalisis tentang 1) Untuk menganalisis stress kerja Pegawai di era digitalisasi perbankan pada Bank Rakyat Indonesia KCP Tasikmalaya. 2) Untuk menganalisis Turnover Intentions Pegawai di era digitalisasi perbankan Bank Rakyat Indonesia KCP Tasikmalaya. 3) Untuk menganalisis besar pengaruh stress kerja terhadap Turnover Intentions Pegawai di era digitalisasi perbankan pada Bank Rakyat Indonesia KCP Tasikmalaya.. Metode penelitian yang digunakan adalah analisis deskriptif dan verifikatif dan mengoperasikan perhitungannya menggunakan program SPSS 26.0. Pengumpulan data yang diperoleh melalui kuesioner, observasi, wawancara, dan studi pustaka. Jumlah populasi relatif kecil atau penelitian yang ingin membuat generalisasi dengan kesalahan yang sangat kecil. Istilah lain sampel jenuh adalah sensus, dimana semua anggota populasi dijadikan sampel, yang dijadikan sampel adalah 67 Pegawai Bank Rakyat Indonesia KCP Tasikmalaya. Hasil penelitian ini menyimpulkan bahwa 1) Stress Kerja yaitu dengan nilai skor terbesar 288, adapun dimensi yang menghasilkan nilai skor terendah yaitu dengan nilai skor sebesar 286 Variabel Stress Kerja menghasilkan nilai rata-rata sebesar 287 dan berada pada garis kontinum 82,0% dengan demikian pernyataan dari Stress Kerja termasuk kategori “Sangat Tinggi”. 2) Turnover Intention yaitu dengan nilai skor terbesar 297, adapun dimensi yang menghasilkan nilai skor terendah yaitu dengan nilai skor sebesar 286 Variabel Turnover Intention menghasilkan nilai rata-rata sebesar 292 dan berada pada garis kontinum 84% dengan demikian pernyataan dari Turnover Intention termasuk kategori “Sangat tinggi/baik”. 3) Terdapat pengaruh sedang dan signifikan sebesar 46,2% dari Stress Kerja terhadap Turnover Intention. Kata Kunci : Stress Kerja, Turnover Intention